Therapeutic approach of natural products that treat osteoporosis by targeting epigenetic modulation - Zhang, Guokai; Liu, Zhenying; Li, Zihan; Zhang, Bing; Yao, Pengyu; Qiao, Yun (Frontiers in Genetics, 2023)
Osteoporosis (OP) is a metabolic disease that affects bone, resulting in a progressive decrease in bone mass, quality, and micro-architectural degeneration. Natural products have become popular for managing OP in recent years due to their minimal adverse side effects and suitability for prolonged use compared to chemically synthesized products. These natural products are known to modulate multiple OP-related gene expressions, making epigenetics an important tool for optimal therapeutic development. In this study, we investigated the role of epigenetics in OP and reviewed existing research on using natural products for OP management. Our analysis identified around 20 natural products involved in epigenetics-based OP modulation, and we discussed potential mechanisms. These findings highlight the clinical significance of natural products and their potential as novel anti-OP therapeutics.